Perilaku Agresi Verbal pada K-Popers : Sebuah Studi Naratif Review tentang hubungannya dengan Celebrity Worship - Sukartiasih, Wayan; Fauzi, Achmad; Arinandia, Luh Putu Oka Putri (LITERATUS, 2024)
Verbal aggressive behavior that occurs among K-popers on social media is usually triggered by the celebrity worship (fanaticism) behavior that individuals have towards K-pop idols. This research aims to determine the relationship between verbal aggression and celebrity worship among K-popers. The method used in this writing uses a narrative review approach. The articles used in this study were taken from three database search engines, namely Crossref, Scopus, and Google Scholar with a total of two articles that met the criteria. All articles used in this study come from 2018 to 2022. The results of this narrative review show that there is a positive relationship and influence between celebrity worship (fanaticism) on verbal aggression among K-popers.